Comment on Gignac and Zajenkowski, “The Dunning-Kruger effect is (mostly) a statistical artefact: Valid approaches to testing the hypothesis with individual differences data” - Hiller, Avram (Intelligence (Norwood), 2023)
Gignac and Zajenkowski (2020) find that “the degree to which people mispredicted their objectively measured intelligence was equal across the whole spectrum of objectively measured intelligence”. This Comment shows that Gignac and Zajenkowski (2020) finding of homoscedasticity is likely the result of a recoding choice by the experimenters and does not in fact indicate that the Dunning-Kruger Effect is a mere statistical artifact. Specifically, Gignac and Zajenkowski (2020) recoded test subjects' responses to a question regarding self-assessed comparative IQ onto a linear IQ scale when a normal IQ scale would likely have been more appropriate. More generally, researchers studying self-assessed intelligence should be aware of potential measurement problems that may arise when transforming an ordinal scale onto an interval scale. •Gignac and Zajenkowski (2020) argue that the DKE is a statistical artifact.•G&Z's finding is likely a result of G&Z's data recoding choice.•Two other related DKE studies raise some similar concerns.•Recoding an ordinal measure onto an interval scale may introduce error.